Management of apixaban anticoagulation in a patient requiring therapeutic plasma exchange: a case report and a literature review - Pilková, A; Hartinger, J M; Malíková, I; Satrapová, V; Šťastná, D; Tesař, V; Slanař, O (Die Pharmazie, 2024)
Therapeutic plasma exchange (TPE) is used as an effective treatment modality for a variety of autoimmune disorders. Apart from its desired effect of removing pathological blood components, it also can remove coagulation factors and drugs. Currently, there is an insufficient amount of information regarding the use of direct oral anticoagulants in this setting. In this article, we present a case report of a patient with myasthenia gravis and chronic anticoagulation with apixaban who underwent a series of TPE while continuing apixaban treatment. We observed that only 10% of daily dose was removed by the procedure and plasma levels of apixaban corresponded with expected range. TPE was not associated with shortened drug plasma half-life. We did not observe any significant alteration of apixaban pharmacokinetics during the period of TPE therapy, as well as no thrombotic or bleeding events. This case report supports the use of apixaban in patients treated by TPE, nevertheless, to firmly establish apixaban efficacy and safety profile in this clinical setting further research is needed.
Keywords: antikoagulancia; Female; pyridony; Half-Life; ženské pohlaví; myasthenia gravis; Anticoagulants; Pyrazoles; lidé; pyrazoly; Pyridones; poločas; Myasthenia Gravis; Male; Factor Xa Inhibitors; Aged; inhibitory faktoru Xa; výměna plazmy; Plasma Exchange; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans